Dynamics of domain wall motion in Y-shaped structures - Chua, Ee Liang (Nanyang Technological University, 2015)
Many devices have been developed based on the concept domain wall propagation either by current or by magnetic fields. Such devices primarily have a single-track structure through which domain walls are able to propagate, however, multiple-track devices are still under development. We investigate the dynamics of domain wall motion in a simple Y-shape branched structure. We have found a directional preference in the propagation of domain walls in the form of applied current. Significantly less current is required to drive a domain wall into its preferred direction, in most cases only half the current is required compared to its alternate direction. The domain wall velocities followed the same relationship as the single- track structures. These were found to be independent of the angle of separation of the Y- shaped structures and the thickness of the structure up to a certain extent.